Draft Eleventh Five Year Plan 2007-2012 Volume-I (Narrative) Government of Rajasthan Planning Department - Planning Commission (Planning Commission, 2007)
Rajasthan's economy is predominantly agrarian and rural in nature and there are wide fluctuations in the growth rate of the net state domestic product due to uncertainties in agricultural production, which is almost entirely dependent on rainfall. The primary sector comprising of Agriculture, Animal Husbandry. Forestry, Fisheries and Mining has been showing mixed trend on year to year, its contribution to the NSDP decreased from 31.23 percent in the year 1999-2000 to 28.16 percent in the year 2005-06. The share of Primary Sector has been the lowest in the year 2002-03, which was a severely drought affected year. The sectoral percentages given in the above table reveal the shift from Primary Sector to Tertiary Sector.
Narrative
Government of Rajasthan